Epidemiological analysis of Trueperella abortisuis isolated from cases of pig abortion of a single farm - Alssahen, Mazen; Hassan, Abdulwahed Ahmed; Wickhorst, Jörn-Peter; Sammra, Osama; Lämmler, Christoph; Glaeser, Stefanie P; Kämpfer, Peter; Timke, Markus; Prenger-Berninghoff, Ellen; Abdulmawjood, Amir (Folia microbiologica, 2020)
The present study was designed to characterize six Trueperella (T.) abortisuis strains, cultured over a period of 5 months from fetus and abortion material of six pigs of a single farm in Mecklenburg-West Pomerania federal state, Germany. It was of interest to investigate the epidemiological relationships of the six strains among each other and whether a single bacterial clone was responsible for the abortion situation of the single farm. All six strains were identified phenotypically, by MALDI-TOF MS analysis and by phylogenetic analysis based on 16S rRNA gene and gap (encoding the glyceraldehyde 3-phosphate dehydrogenase) and tuf (encoding elongation factor tu) gene sequencing. Further genotypic comparison was performed using different genomic DNA fingerprint methods including BOX-PCR, (GTG)5-PCR, and three RAPD-PCRs. The sequence analysis of the genes gap and tuf and the genomic DNA fingerprinting results revealed, as noval findings, that the six T. abortisuis strains cultured from a single farm represent six different bacterial clones showing a genetic variability of this bacterial species in the pig population. All six T. abortisuis strains were isolated in mixed culture with several other bacterial species. However, the T. abortisuis strain, generally found in high numbers, seemed to be responsible for the abortion situation in the farm.
Keywords: prasata; Swine; fenotyp; Male; Phenotype; genetická variace; Genotype; fylogeneze; Abortion, Veterinary; RNA, Ribosomal, 16S; Sequence Analysis, DNA; Phylogeny; infekce bakteriemi řádu Actinomycetales; Pregnancy; těhotenství; sekvenční analýza DNA; DNA fingerprinting; DNA Fingerprinting; mužské pohlaví; potrat u zvířat; potracený plod; Actinomycetaceae; Actinomycetales Infections; Germany; Animals; farmy; ženské pohlaví; nemoci prasat; zvířata; Aborted Fetus; Německo; Swine Diseases; RNA ribozomální 16S; genotyp; Farms; Genetic Variation; Female